High-strength and high-conductivity copper alloy with fine grain structure and preparation method of high-strength and high-conductivity copper alloy

By in-situ synthesis of micron-scale particles and deformation heat treatment processes in Cu-Ni-Si alloys, high-strength and high-conducting copper alloys with fine crystal structures are prepared, which solves the problem of the improvement of the strength of the existing alloys, and achieves the comprehensive performance of high strength, excellent conductivity and good plasticity and toughness.

CN119824274APending Publication Date: 2025-04-15NORTH CHINA ELECTRIC POWER UNIV +1
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411925295.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

When the strength of existing Cu-Ni-Si alloys increases, their conductivity and plastic toughness will decrease, and their processability will be poor, making it difficult to meet the needs of high integration, high precision, miniaturization and lightweight electronic components.

Method used

By synthesizing uniformly distributed micron-scale granular phases in situ during the melt casting process, using the synergistic action of Ni16Ti6Si7, TiB2, and Ni2Si particles, combined with the deformation heat treatment process, a high-strength and high-conducting copper alloy with fine crystal structure was prepared.

Benefits of technology

On the basis of ensuring conductivity and high strength, the plasticity and toughness of copper alloys are improved, the tensile strength reaches 400-1100MPa, the conductivity reaches 20%-80% IACS, and the elongation is greater than 8%, which is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824274A_ABST
    Figure CN119824274A_ABST
Patent Text Reader

Abstract

The invention provides a high-strength and high-conductivity copper alloy with a fine grain structure and a preparation method of the high-strength and high-conductivity copper alloy, and belongs to the technical field of copper alloy preparation. The copper alloy comprises the following elements in percentage by mass: 2.0-12.0 wt.% of Ni, 0.4-3.0 wt.% of Si, less than or equal to 1.0 wt.% of Zn, less than or equal to 5.0 wt.% of Ti, less than or equal to 1.0 wt.% of B and the balance of Cu and inevitable impurities. According to the method, the heat treatment process is adjusted, generation of Ni16Ti6Si7 and TiB2 phases is promoted through introduction of Ti and B elements, micron-sized particles can serve as nucleation sites and pinning grain boundaries in the heat deformation process, and grain refinement is promoted. The high-strength and high-conductivity copper alloy with a fine grain structure is obtained by changing the content of Ti and B elements in the copper alloy and regulating and controlling the proportion of Ni16Ti6Si7, a TiB2 micron phase and a Ni2Si nano phase.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of copper alloy preparation, and in particular to a high-strength and high-conductivity copper alloy with a fine-grained structure and a preparation method thereof. Background Art

[0002] Cu-Ni-Si alloy is widely used in integrated circuit packaging, semiconductor lead frames, new energy vehicle connectors and other fields due to its low cost, high strength, and good electrical and thermal conductivity. The good conductivity and strength are attributed to nano-δ-Ni 2 Precipitation of Si phase. In recent years, as electronic components have developed towards high integration, high precision, miniaturization and lightweight, higher requirements have been placed on the comprehensive performance of Cu-Ni-Si alloys, including machinability.

[0003] Improving the strength of precipitation-hardened copper alloys is inevitably accompanied by a decrease in electrical conductivity and ductility. As an aging-hardened copper alloy, the precipitated phase of Cu-Ni-Si alloy after aging treatment is mainly composed of Ni 2 Si and Ni 3 Si composition. The high-density precipitated phase will not only strengthen the alloy, but also split the matrix, affecting the plasticity and toughness of the alloy. In addition, the work hardening caused by the accumulation of a large number of dislocations during the deformation process also greatly affects the machinability of the alloy.

[0004] Since the slip resistance near the grain boundary is large, the electrical conduction of the crystal is independent of the orientation of the grains, so grain refinement has little effect on the electrical conductivity of the alloy. In addition, grain refinement can reduce the stress concentration caused by the accumulation of dislocations at the grain boundaries during metal deformation, delay the formation of cracks, and help improve the plasticity and toughness of the material. In recent years, the preparation of materials with fine grain structure by adding trace amounts of third elements and changing the aging process has become an important copper alloy design and preparation concept.

[0005] Therefore, based on the concept of fine grain strengthening, by rationally designing the components of the Cu-Ni-Si alloy to form fine and dispersed refractory particles, and by using a series of deformation and heat treatment methods to limit the migration of grain boundaries and dislocations, while ensuring the excellent conductivity and high strength of the copper alloy, by optimizing the dynamic recrystallization behavior of the alloy, obtaining a high-strength and high-conductivity Cu-Ni-Si alloy with a fine grain structure is the current key research direction in this field. This invention will provide new ideas for the research and development of copper alloys and provide more powerful support for the industrial development of copper alloys. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides a high-strength and high-conductivity copper alloy with a fine-grained structure and a preparation method thereof. The present invention synthesizes a uniformly distributed micron-sized granular phase in situ during the melting and casting process; based on Ni 16 Ti 6Si 7 , TiB 2 、Ni 2 The synergistic effect of Si particles enables the copper alloy to have excellent comprehensive properties, including a tensile strength of 400-1100 MPa, a conductivity of 20%-80% IACS, and an elongation of more than 8%.

[0007] The high-strength and high-conductivity copper alloy with fine-grained structure of the present invention comprises the following elements in mass percentage: Ni 2.0-12.0wt.%, Si 0.4-3.0wt.%, Zn≤1.0wt.%, Ti≤5.0wt.%, B≤1.0wt.%, and the rest are Cu and unavoidable impurities.

[0008] Preferably, the average grain size of the copper alloy is 5-20 μm, and the number of grains with a grain size greater than 50 μm accounts for ≤5%.

[0009] The method for preparing the high-strength and high-conductivity copper alloy with fine-grained structure comprises the following steps:

[0010] (1) Alloy smelting: weigh the raw materials in proportion and add them into the medium frequency induction furnace in sequence for smelting to form a copper-based melt;

[0011] (2) alloy casting: the copper-based melt obtained in step (1) is kept at 1270-1300° C. for 2-10 min, deslagging with cryolite, and then cast in a cylindrical mold and cooled to obtain a copper alloy ingot;

[0012] (3) Thermomechanical treatment process: The copper alloy ingot prepared in step (2) is subjected to homogenization annealing → hot deformation → solution treatment → quenching → milling → primary cold deformation → pre-aging → secondary cold deformation → secondary aging treatment to obtain the high-strength and high-conductivity copper alloy with a fine grain structure.

[0013] Preferably, the smelting temperature in step (1) is 1260-1350°C.

[0014] Preferably, the smelting in step (1) is performed by vacuum smelting; the vacuum is achieved by covering with charcoal or filling with Ar gas.

[0015] Preferably, the amount of cryolite added in step (2) is 0.2% of the total mass of the alloy; and the cooling rate is 100-160K / S.

[0016] Preferably, the temperature of the homogenization annealing in step (3) is 900-1025° C., and the holding time is 3-8 h;

[0017] The solid solution temperature is 900-1000°C and the holding time is 1-4h;

[0018] The pre-aging temperature is 400-550°C, and the holding time is 0.5-4h;

[0019] The secondary aging temperature is 350-500° C., and the insulation time is 0.5-16 hours.

[0020] Preferably, the thermal deformation temperature in step (3) is 900-1025° C., and the total processing rate is 40-95%;

[0021] The cold deformation temperature is 20-35° C., and the total processing rate is 30-90%.

[0022] Preferably, the deformation process in step (3) can be one or more of rolling, extrusion, forging and drawing.

[0023] Preferably, the deformation heat treatment process in step (3) is: subjecting the copper alloy ingot prepared in step (2) to homogenization annealing → hot deformation → solution treatment → quenching → milling → cold deformation → aging treatment to obtain the high-strength and high-conductivity copper alloy with fine grain structure.

[0024] The metal elements in the present invention have the following functions:

[0025] Zn: Zn has a large solid solubility in Cu and can form a continuous solid solution with Cu. It has a wide single-phase region, which can avoid the looseness in the ingot and significantly improve the mechanical properties and corrosion resistance of Cu. A small amount of Zn can also prevent Si and Ti elements from combining with oxygen to produce SiO 2 and TiO 2 Oxides, reducing the generation of oxide inclusions in the melt. During brazing, Zn can improve the microstructure of the alloy and solder interface and improve the welding performance of the alloy. However, the amount of Zn added needs to be controlled, not exceeding 1.0wt.%, otherwise the performance of the alloy will deteriorate.

[0026] Ti: The addition of Ti can reduce the grain size of Cu alloy and significantly increase the elongation of the alloy. In Cu-Ni-Si alloy, the introduction of trace Ti will also accelerate the 2 The precipitation and growth of Si phase are beneficial to the improvement of conductivity. Since the solid solubility of Ti in copper is small, excessive addition can promote Ni 16 Ti 6 Si 7 The phase is synthesized in situ and acts as a nucleation site and pins the grain boundaries during hot deformation, further promoting grain refinement.

[0027] B: The solid solubility of B in Cu is very low. The residual B can refine the grains and improve the recrystallization degree of the alloy, and the electrical conductivity of the alloy does not decrease significantly. In addition, in Cu-Ni-Si-Ti alloy, B element can also refine Ni 16 Ti6 Si 7 The particles are more uniform and fine micron-sized phases are obtained during the melting and casting process. 2 with Ni 16 Ti 6 Si 7 It can play a synergistic role in refining alloy grains.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. Low preparation cost, simple and stable process, high efficiency, suitable for industrial large-scale production;

[0030] 2. Micron-sized Ni generated in the alloy 16 Ti 6 Si 7 Phase and TiB 2 Phase distribution is regular, and the size is uniform and controllable;

[0031] 3. Nano-scale Ni generated in the alloy 16 Ti 6 Si 7 With Ni 2 The Si phase is small and uniform in size, precipitated in situ in the matrix, and has good interface bonding;

[0032] 4. Based on deformation heat treatment process and Ni 16 Ti 6 Si 7 , TiB 2 、Ni 2 The synergistic effect of Si particles, the average grain size of the copper alloy is 5-20μm, the number of grains with a grain size greater than 50μm accounts for ≤5%, the tensile strength reaches 400-1100MPa, the conductivity reaches 20%-80% IACS, and the elongation is greater than 8%. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a scanning electron microscope image of the cast microstructure of the high-strength and high-conductivity copper alloy with fine grain structure prepared in Example 1;

[0034] Figure 2 This is a microstructure diagram of grain corrosion of a high-strength and high-conductivity copper alloy with a fine-grained structure prepared in Example 1;

[0035] Figure 3 This is a scanning electron microscope image of the cast microstructure of the high-strength and high-conductivity copper alloy with fine grain structure prepared in Example 2;

[0036] Figure 4 This is a grain corrosion microstructure diagram of the high-strength and high-conductivity copper alloy with fine grain structure prepared in Example 2.

[0037] Figure 5 This is the grain corrosion microstructure diagram of the high-strength and high-conductivity copper alloy prepared in Comparative Example 1. DETAILED DESCRIPTION

[0038] The present invention will be further described below in conjunction with the embodiments.

[0039] Example 1

[0040] A high-strength and high-conductivity copper alloy with a fine-grained structure is composed of the following elements in mass percentage: 3.20wt.%, 0.70wt.%, 0.55wt.%, and the remainder is Cu and inevitable impurities.

[0041] The method for preparing the high-strength and high-conductivity copper alloy with fine grain structure comprises the following steps:

[0042] (1) Alloy smelting: copper, nickel block, pure silicon wafer and titanium sponge were weighed in a weight ratio of 95.59:3.20:0.70:0.55, and added to a medium frequency induction furnace in sequence for smelting at 1320°C. The smelting process was carried out in an Ar gas environment with charcoal added to form a copper-based melt;

[0043] (2) alloy casting: the copper-based melt obtained in step (1) is kept at 1300° C. for 10 min, and is adsorbed by cryolite with a total mass of 0.2 wt.% of the alloy and is manually deslagging before casting and cooling in a cylindrical mold to obtain a copper alloy ingot; the cooling rate is 125 K / s;

[0044] (3) Thermomechanical heat treatment process: the copper alloy ingot prepared in step (2) is heated to 1000°C for homogenization annealing for 4 hours, and then hot rolled at 1000°C for 80%, and after hot rolling, solid solution is carried out at 1000°C for 4 hours, and then water-cooled quenching is performed, and surface oxides are milled off and then cold rolled and aging heat treated to obtain a high-strength and high-conductivity copper alloy with a fine grain structure;

[0045] The cold rolling and aging heat treatment includes primary cold deformation → pre-aging → secondary cold deformation → secondary aging treatment, the cold deformation temperature is 20-35°C, and the specific steps are as follows: primary cold rolling of 60%, and pre-aging at 450°C for 1h, followed by secondary cold rolling of 50%, and secondary aging at 450°C for 2h, to obtain the high-strength and high-conductivity copper alloy with fine grain structure.

[0046] The as-cast microstructure of the prepared fine-grained high-strength and high-conductivity copper alloy is shown in the attached figure. Figure 1 As shown in the attached figure, the grain corrosion diagram Figure 2As shown. According to the performance test, the prepared alloy has a tensile strength of 702.1MPa, a conductivity of 43%IACS, an average grain size of 6.15μm, and a grain size greater than 50μm, accounting for ≤2%. The elongation is maintained at 8.75%.

[0047] Example 2

[0048] A high-strength and high-conductivity copper alloy with a fine-grained structure is composed of the following elements in percentage by mass: 3.20wt.%, 0.71wt.%, 0.10wt.%, 0.50wt.%, 0.05wt.%, and the remainder is Cu and unavoidable impurities.

[0049] The method for preparing the high-strength and high-conductivity copper alloy with fine grain structure comprises the following steps:

[0050] (1) Alloy smelting: copper, nickel block, pure silicon wafer, titanium sponge, Cu-5B master alloy and zinc block were weighed in a weight ratio of 95.59:3.20:0.71:0.50:1.00:0.10, and added to a medium frequency induction furnace in sequence for smelting at 1300° C. The smelting process was carried out in an Ar gas environment with charcoal added to form a copper-based melt;

[0051] (2) Alloy casting: The copper-based melt obtained in step (1) is kept at 1280° C. for 5 min, and is adsorbed by cryolite with a total mass of 0.2 wt.% of the alloy, and after manual slag removal, is cast in a cylindrical mold and cooled to obtain a copper alloy ingot; the cooling rate is 140 K / s;

[0052] (3) Thermomechanical heat treatment process: the copper alloy ingot prepared in step (2) is heated to 1000°C for homogenization annealing for 3 hours, and then hot rolled at 1000°C for 80%, and after hot rolling, solid solution is carried out at 1000°C for 4 hours, and then water-cooled quenching is performed, and surface oxides are milled off and then cold rolled and aging heat treated to obtain a high-strength and high-conductivity copper alloy with a fine grain structure;

[0053] The cold rolling and aging heat treatment includes cold deformation → aging treatment, the cold deformation temperature is 20-35°C, and the specific steps are as follows: cold rolling 60%, and aging at 450°C for 6h to obtain the high-strength and high-conductivity copper alloy with fine grain structure.

[0054] The as-cast microstructure of the prepared fine-grained high-strength and high-conductivity copper alloy is shown in the attached figure. Figure 3 As shown in the attached figure, the grain corrosion diagram Figure 4 According to the performance test, the prepared alloy has a tensile strength of 716.7MPa, a conductivity of 42%IACS, an elongation of 9.87%, an average grain size of 7.34μm, and a grain size greater than 50μm of ≤3%.

[0055] Comparative Example 1

[0056] According to the preparation process of Example 2, red copper, nickel block and pure silicon wafer were weighed in a weight ratio of 96.10:3.20:0.70 to prepare a Cu-Ni-Si alloy.

[0057] The grain corrosion diagram of the prepared high strength and high conductivity Cu-Ni-Si alloy is shown in the attached figure. Figure 5 As shown. It can be seen that the prepared Cu-Ni-Si alloy has a larger grain size. According to performance tests, the prepared alloy has a tensile strength of 766MPa, a conductivity of 34%IACS, an elongation of 7.50%, an average grain size of 14.65μm, and a grain size greater than 50μm. The number of grains accounts for more than 5%. Therefore, compared with the Cu-Ni-Si alloy, the introduction of Ti and B elements effectively refines the grains of the alloy and prepares a high-strength and high-conductivity copper alloy with a fine-grained structure.

[0058] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A high-strength and high-conductivity copper alloy with fine grain structure, characterized in that: The copper alloy comprises the following elements in mass percentage: Ni 2.0-12.0wt.%, Si 0.4-3.0wt.%, Zn≤1.0wt.%, Ti≤5.0wt.%, B≤1.0wt.%, and the rest are Cu and unavoidable impurities.

2. The high-strength and high-conductivity copper alloy with fine grain structure according to claim 1, characterized in that: The average grain size of the copper alloy is 5 to 20 μm, and the number of grains with a grain size greater than 50 μm accounts for ≤5%.

3. The method for preparing a high-strength and high-conductivity copper alloy with a fine-grained structure according to claim 1 or 2, characterized in that: The following steps are involved: (1) Alloy smelting: weigh the raw materials in proportion and add them into the medium frequency induction furnace in sequence for smelting to form a copper-based melt; (2) alloy casting: the copper-based melt obtained in step (1) is kept at 1270-1300° C. for 2-10 min, deslagging with cryolite, and then cast in a cylindrical mold and cooled to obtain a copper alloy ingot; (3) Thermomechanical treatment process: The copper alloy ingot prepared in step (2) is subjected to homogenization annealing → hot deformation → solution treatment → quenching → milling → primary cold deformation → pre-aging → secondary cold deformation → secondary aging treatment to obtain the high-strength and high-conductivity copper alloy with a fine grain structure.

4. The method for preparing a high-strength and high-conductivity copper alloy with a fine-grained structure according to claim 3, characterized in that: The smelting temperature in step (1) is 1260-1350°C.

5. The method for preparing a high-strength and high-conductivity copper alloy with a fine-grained structure according to claim 3, characterized in that: The smelting in step (1) is performed by vacuum smelting; the vacuum is achieved by covering with charcoal or filling with Ar gas.

6. The method for preparing a high-strength and high-conductivity copper alloy with a fine-grained structure according to claim 3, characterized in that: In step (2), the amount of cryolite added is 0.2% of the total mass of the alloy; and the cooling rate is 100-160K / s.

7. The method for preparing a high-strength and high-conductivity copper alloy with a fine-grained structure according to claim 3, characterized in that: The homogenization annealing temperature in step (3) is 900-1025° C., and the holding time is 3-8 hours; The solid solution temperature is 900-1000°C and the holding time is 1-4h; The pre-aging temperature is 400-550°C, and the holding time is 0.5-4h; The secondary aging temperature is 350-500° C., and the insulation time is 0.5-16 hours.

8. The method for preparing a high-strength and high-conductivity copper alloy with a fine-grained structure according to claim 3, characterized in that: The thermal deformation temperature of step (3) is 900-1025° C., and the total processing rate is 40-95%; The cold deformation temperature is 20-35° C., and the total processing rate is 30-90%.

9. The method for preparing a high-strength and high-conductivity copper alloy with a fine-grained structure according to claim 3, characterized in that: The deformation process in step (3) can be one or more of rolling, extrusion, forging and drawing.

10. The method for preparing a high-strength and high-conductivity copper alloy with a fine-grained structure according to claim 3, characterized in that: The thermomechanical treatment process of step (3) is as follows: subjecting the copper alloy ingot prepared in step (2) to homogenization annealing → thermal deformation → solution treatment → quenching → milling → cold deformation → aging treatment to obtain the high-strength and high-conductivity copper alloy with fine grain structure.

Citation Information

Cited By

  • Cu-Cr-Zr-TiB2 copper-based composite material as well as preparation method and application thereof

    CN120169871A

  • A Cu-Cr-Zr-TiB2 copper matrix composite material, its preparation method and application

    CN120169871B

  • High-conductivity copper alloy material for cable as well as preparation process and application of high-conductivity copper alloy material

    CN120464903A